Carbon sequestration ability of Quercus robur L. plantation in Feofania Park, Kyiv (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
Сarbon sequestration in young pedunculate oak (Quercus robur L.) trees stems growing in a Feofania Park stand were reconstructed in this article. We used standard dendrochronological approaches to obtain tree-ring and basal area chronologies (1932–2015). The mean radial growth rate of studied trees at age 65 was 3.18±1.06 mm per year and ranged from 1.86 to 5.49 mm per year. In 2015, a carbon mass in an oak stem reached mean value of 366±176 kg and ranged between 167 and 922 kg depending from a stem diameter. Pedunculate oak fixating ability increases from 2 and 5 kg carbon per year at age 20 and 30 to 10 kg carbon per year at 45–72.
Keywords: radial growth, pedunculate oak, carbon storage.